Short-Term Effect of Continuous Subcutaneous Insulin Infusion and Multiple Daily Injection in Perioperative Patients with Type 2 Diabetes Mellitus - Wei Song; Jianxuan Wen; Jinming Zhang; Meng Luo; Yue Hu; Yu Zhang; Guanjie Fan; Ling Zhao (Journal of Diabetes Research)
Background. Hyperglycemia is common and difficult to control in perioperative patients with type 2 diabetes mellitus (T2DM), which impacts their prognosis after operation. Our study investigated the short-term effect of continuous subcutaneous insulin infusion (CSII) and multiple daily injection (MDI) in perioperative T2DM patients using the data envelopment analysis (DEA). Methods. T2DM patients (n=639) who underwent surgeries in Guangdong Provincial Hospital of Traditional Chinese Medicine (2009.01-2017.12) were included. Insulin was provided to each patient during the study and separated into a CSII group (n=369) and an MDI group (n=270). DEA was performed to compare the therapeutic indexes and investigate the short-term effect of the CSII group and MDI group. Results. Scale efficiencies of the CSII group with CCR model and BCC model were better than that of the MDI group. Regarding slack variables, with higher surgical levels, the CSII group was closer to the ideal state than the MDI group, which indicated in improving the average fasting blood glucose (AFBG), antibiotic use days (AUD), preoperative blood glucose control time (PBGCT), first postoperative day fasting blood glucose (FPDFBG), and postoperative hospitalization days (PHD). Conclusion. CSII could effectively control blood glucose levels and shorten perioperative hospitalizing time for T2DM patients, indicating that CSII was beneficial in perioperative period and should be promoted clinically.